Stress and Traumatic Brain Injury: A Behavioral, Proteomics, and Histological Study - Kwon, Sook-Kyung C.; Kovesdi, Erzsebet; Gyorgy, Andrea B.; Wingo, Daniel; Kamnaksh, Alaa; Walker, John; Long, Joseph B.; Agoston, Denes V. (Frontiers in Neurology, 2011)
Psychological stress and traumatic brain injury (TBI) can both result in lasting neurobehavioral abnormalities. Post-traumatic stress disorder (PTSD) and blast induced TBI (bTBI) have become the most significant health issues in current military conflicts. Importantly, military bTBI virtually never occurs without stress. In this experiment, we assessed anxiety and spatial memory of rats at different time points after repeated exposure to stress alone or in combination with a single mild blast. At 2 months after injury or sham we analyzed the serum, prefrontal cortex (PFC), and hippocampus (HC) of all animals by proteomics and immunohistochemistry. Stressed sham animals showed an early increase in anxiety but no memory impairment at any measured time point. They had elevated levels of serum corticosterone (CORT) and hippocampal IL-6 but no other cellular or protein changes. Stressed injured animals had increased anxiety that returned to normal at 2 months and significant spatial memory impairment that lasted up to 2 months. They had elevated serum levels of CORT, CK-BB, NF-H, NSE, GFAP, and VEGF. Moreover, all of the measured protein markers were elevated in the HC and the PFC; rats had an increased number of TUNEL+ cells in the HC and elevated GFAP and Iba1 immunoreactivity in the HC and the PFC. Our findings suggest that exposure to repeated stress alone causes a transient increase in anxiety and no significant memory impairment or cellular and molecular changes. In contrast, repeated stress and blast results in lasting behavioral, molecular, and cellular abnormalities characterized by memory impairment, neuronal and glial cell loss, inflammation, and gliosis. These findings may have implications in the development of diagnostic and therapeutic measures for conditions caused by stress or a combination of stress and bTBI.